2021
DOI: 10.17584/rcch.2021v15i3.13159
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and growth components of feijoa (Acca sellowiana [O. Berg] Burret) plants in response to the missing elements N, P, and K

Abstract: Plants often express deficiencies with visible abnormalities; however, it is necessary to obtain reliable information to make the proper diagnosis about the missing nutrients. Until now, research with this approach has not been carried out for crops such as feijoa (or pineapple guava). For this reason, the present investigation identified and described the symptoms produced in young feijoa plants due to poor fertilization of N, P, and K and its effect on some components of plant growth and development. To achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The observed symptoms are consistent with Souza de Miranda et al [ 31 ] reported in cowpea and Buitrago et al [ 14 ] in feijoa. The generalized chlorosis in adult leaves and the pale green coloration of the leaves are due to the mineral element's high mobility and the loss of chlorophyll that requires N as an essential constituent [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The observed symptoms are consistent with Souza de Miranda et al [ 31 ] reported in cowpea and Buitrago et al [ 14 ] in feijoa. The generalized chlorosis in adult leaves and the pale green coloration of the leaves are due to the mineral element's high mobility and the loss of chlorophyll that requires N as an essential constituent [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Kochhar and Gujral [ 49 ] described the similar symptoms in this experiment. Excess anthocyanins in some plant species give rise to a slightly purplish color in leaves [ 50 , 51 ], and the dark green color occurs because leaf expansion is inhibited to a greater extent than chlorophyll formation [ 52 ]; Meanwhile, malformations are due to the lack of energy to complete mitosis, thus limiting the correct formation of photosynthetic organs [ 14 ]. When P levels are low in foliar tissues, cell division rates are reduced, affecting tissue expansion, which restricts aerial sprouting and causes a rearrangement in the distribution of photoassimilates to the different plant organs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of nutrient uptake are more common in the international literature for annual crops such as vegetables (Adiele et al, 2021) and cereals (Silva et al, 2021), but they are very rare for fruit crops (Buitrago et al, 2021), especially star fruit. This is due to high added value and increasing demand of the international fruit markets.…”
mentioning
confidence: 99%
“…The fruit are yellow berries at harvest, approximately 25 g, with a very good taste and aroma (Álvarez-Herrera et al, 2009a), which are consumed fresh or in derived products and are highly desired by consumers. C. lineatifolia has a high commercial potential, as seen in other myrtaceae such as arazá (Eugenia stipitata; Carrillo et al, 2011), gabiroba (Campomanesia adamantium; Do Santos et al, 2021), feijoa (Acca sellowiana; Buitrago et al, 2021) and guava (Psidium guajava; Fischer and Melgarejo, 2021). It is being introduced in the different markets of Colombia (Balaguera-López and Herrera, 2012a; Porras et al, 2020).…”
mentioning
confidence: 99%